Automated external defibrillator: Rhythm analysis and defibrillation on paediatric out-of-hospital cardiac arrest - Emma Menant; Delphine Lavignasse; Sarah Ménétré; Jean-Philippe Didon; Xavier Jouven (Resuscitation Plus)
Objective: This study aims to quantify the reliability of automated external defibrillators (AED) in paediatric out-of-hospital cardiac arrests (pOHCA) by evaluating the defibrillation and the shock advisory system efficacy. Furthermore, the relationship between the initial energy dose and patient outcomes is analysed. Methods: We studied data from all pOHCA cases (age < 18 years) treated by the Paris Fire Brigade between January 2010 and December 2018, limited to those with available AED signals. The efficacy of shocks is the primary outcome. The secondary outcomes are the shock advisory system performance, pre-hospital return of a spontaneous circulation (ROSC), survival and energy dose. Energy dose, weight and age are compared using a Wilcoxon test according to the outcome’s values. Results: A total of 1,990 electrocardiogram strips extracted from 349 pOHCA cases were included in the study. Shock advisory system had a sensitivity of 89.4% and a specificity of 99.8% for the detection of shockable rhythms. Shock efficacy observed for all patients who received a shock was 83.1% and first shock efficacy for patients in initial ventricular fibrillation was 96%. Patients who received a shock had a pre-hospital ROSC rate of 74.3%, a survival rate at hospital admission of 71.4% and 34.3% at hospital discharge. Conclusion: This study shows that AED detect shockable rhythm with a good sensitivity and specificity and that shocks are associated with a very high rates of termination of shockable rhythms in pOHCA.